Sex differences in the mediation of the MASLD - Depression association by fat distribution in U.S. adults - Changhuai He; Liuxin Zhou; Tianming Gao; Runmin Cao; Chuanqi Cai; Guoqing Jiang (Acta Psychologica)
Purpose: This study investigates the intricate relationship between metabolic dysfunction-associated steatotic liver disease (MASLD) and depression, emphasizing the mediating role of body fat distribution, particularly in female. Methods: We analyzed the pairwise relationship among body fat distribution (android fat and gynoid fat), MASLD, and depression within a robust, ethnically diverse sample (n = 3332) drawn from the National Health and Nutrition Examination Survey (NHANES). Results: Studies have indicated that individuals with depression or MASLD exhibit significantly higher levels of android fat compared to those without these health issues. Even after controlling for confounding factors, MASLD maintained significant correlations with both depression and body fat distribution (android fat and gynoid fat). Notably, sex moderated the relationship between MASLD, depression, and body fat distribution. Among the potential mediators of the effect of MASLD on depression, android fat emerged as a significant mediator, accounting for 16.6 % of the variance and yielding statistically significant results (p < 0.05). This mediating effect was particularly pronounced in female subjects, with a mediating proportion of 17.83 %, which was also statistically significant (p < 0.05). However, it was not observed in males. Conclusions: This study reveals an important association between MASLD and depression, and android fat distribution is a potential mediator in this relationship, with a particularly pronounced effect on the female population.